2003
DOI: 10.1021/ol034787k
|View full text |Cite
|
Sign up to set email alerts
|

Silylative Carbocyclization of Allenyl-carbonyl Units with Et3SiH Catalyzed by Rhodium:  Cis-Stereoselective Synthesis of Homoallylic Cycloalkanols

Abstract: [reaction: see text] A new procedure for the synthesis of cis-2-triethylsilylvinyl-cyclopentanols and -cyclohexanols from allenyl-aldehydes and -ketones with Et(3)SiH through rhodium-catalyzed silylative carbocyclization is described. The use of Rh(acac)(CO)(2) (1 mol %) to promote the reaction results in a mild and convenient protocol for the three-component assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The cis (δ 5.28-5.37) and trans (δ 5.65-5.75) protons relative to silicon of α-triethylsilyl vinylsilanes are quite distinct, both for other substrates in this study, and in closely related 1-cyclohexenyl-triethylvinylsilane reported elsewhere. 28 This result indicates that the trans addition phenomenon is general-that it applies to terminal alkynes in addition to internal alkynes. The importance of the result with the sterically demanding terminal alkynes is mechanistically significant.…”
Section: (1)mentioning
confidence: 92%
“…The cis (δ 5.28-5.37) and trans (δ 5.65-5.75) protons relative to silicon of α-triethylsilyl vinylsilanes are quite distinct, both for other substrates in this study, and in closely related 1-cyclohexenyl-triethylvinylsilane reported elsewhere. 28 This result indicates that the trans addition phenomenon is general-that it applies to terminal alkynes in addition to internal alkynes. The importance of the result with the sterically demanding terminal alkynes is mechanistically significant.…”
Section: (1)mentioning
confidence: 92%
“…Yu et al observed a Rh-catalyzed silylcarbocyclization of allenyl aldehydes and ketones 841 via the silylrhodation of the allene-1,2-addition to the CO bond-reductive elimination mechanism to afford 2-vinylic cyclic alcohols cis - 842 . Recently, Shibata et al.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…The transition metal‐catalyzed allylation of aldehydes and imines has attracted considerable attention due to the synthetic utility of corresponding homoallylic alcohol and amine products as well as the interesting reactivity of the allyl‐transition metal complex during the reaction 1,2,3,4. To accomplish such allylations using a catalytic amount of transition metal complexes and allylic acetates or allenes as starting materials, a range of protocols utilizing stoichiometric amounts of organometallic reagents (tin,2a,b,d,e,3c zinc,2c,h,i,j,m,p indium,2f,3a,b borane,2o,s,t,u and silane2k,q,r) which reverse the reactivity of the allyl‐metal complexes from electrophilic to nucleophilic have been investigated. Recently, the reactions of nucleophilic allyl‐iridium complexes were reported under transfer hydrogenation conditions where the use of metallic reductants were avoided 5…”
Section: Optimization Of the Reductive Cyclization Of Allene‐aldehydementioning
confidence: 99%